Binding-protein expression is subject to temporal, developmental and stress-induced regulation in terminally differentiated soybean organs - Kalinski, A; Rowley, D.L; Loer, D.S; Foley, C; Buta, G; Herman, E.M. (US Dept. of Agriculture, Beltsville, Maryland (USA). Plant Molecular Biology Dept.) (Planta, 1995)
Binding protein (BiP) is a widely distributed and highly conserved endoplasmic-reticulum luminal protein that has been implicated in cotranslational folding of nascent polypeptides, and in the recognition and disposal of misfolded polypeptides. Analysis of cDNA sequences and genomic blots indicates that soybeans (Glycine max L. Merr.) possess a small gene family encoding BiP. The deduced sequence of BiP is very similar to that of other plant BiPs. We have examined the expression of BiP in several different terminally differentiated soybean organs including leaves, pods and seed cotyledons. Expression of BiP mRNA increases during leaf expansion while levels of BiP protein decrease. Leaf BiP mRNA is subject to temporal control, exhibiting a large difference in expression in a few hours between dusk and night. The expression of BiP mRNA varies in direct correlation with accumulation of seed storage proteins. The hybridization suggests that maturing-seed BiP is likely to be a different isoform from vegetative BiPs. Levels of BiP protein in maturing seeds vary with BiP mRNA. High levels of BiP mRNA are detected after 3 d of seedling growth. Little change in either BiP mRNA or protein levels was detected in maturing soybean pods, although BiP-protein levels decrease in fully mature pods. Persistent wounding of leaves by whiteflies induces massive overexpression of BiP mRNA while only slightly increasing BiP-protein levels. In contrast single-event puncture wounding only slightly induces additional BiP expression above the temporal variations. These observations indicate that BiP is not constitutively expressed in terminally differentiated plant organs. Expression of BiP is highest during the developmental stages of leaves, pods and seeds when their constituent cells are producing seed or vegetative storage proteins, and appears to be subject to complex regulation, including developmental, temporal and wounding.